Identification of Mutated Peptides in Bladder Cancer From Exomic Sequencing Data Reveals Negative Correlation Between Mutation-Specific Immunoreactivity and Inflammation - Wang, Chen; Ding, Yu; Liu, Yuanyong; Zhang, Qingchen; Xu, Shiqiang; Xia, Liliang; Duan, Huangqi; Wang, Shujun; Ji, Ping; Huang, Weiren; Zhao, Guoping; Cao, Zhiwei; et al. (Frontiers in Immunology, 2020)
Introduction and Objective Neoantigen-based immunotherapy is one of the breakthroughs in cancerimmunologytherapy. Benefit from the Cancer Genome Atlas database, we intended to identify mutant peptides with neoantigen property in bladder cancer (BC). Correlations between the immunoreactivity of candidate neoantigens and clinical manifestations were further analyzed. Methods HLA-A*02:01 restricted mutant (MT) and wildtype (WT) peptides were predicted by using whole exome sequencing data of 412 BC patients in the TCGA database. Binding affinity to HLA-A2 molecules was determined by using T2 cell-based binding assay. The immunoreactivity to WT and MT peptides in HLA-A2+ BC patients was determined by using an ELISPOT assay upon in vitro stimulation with MT and WT peptides individually. Clinical relevance to peptide-specific immunoreactivity was analyzed by Pearson correlation analysis. The disease free survival (DFS) curves were plotted using the Kaplan–Meier method in BC patients with or without mutations and compared using the log-rank test online. Results Fifty-seven HLA-A*02:01 restricted WT and MT peptides were selected based on predicted high affinity and expression frequency, among which 12 MT peptides from 12 individual genes exhibited strong affinity to HLA-A2 molecules when compared to WT counterparts. MT peptides induced more peptide-specific IFNγ spot forming units (SFUs) than WT counterparts in HLA-A2+ BC patients upon in vitro stimulation. They were negatively correlated to the counts of peripheral leukocytes and platelets. Patients with higher C-reactive protein level exhibited lower immunoreactivity to MT peptides. Combination of MT peptides from 6 genes, including CDKN1AG61V, RHOBP75L, DDB1S25L, AHNAKD4855Y, ANP32AS56L and MKI67H84L covered 47.5% of the patients under investigation. Patients harboring combinational mutations in these genes were associated with a longer DFS according to the cBioportal online analysis. Conclusion Twelve HLA-A*02:01 restricted MT peptides have been identified exhibiting higher binding affinity to HLA-A2 molecules and stronger immunoreactivity than WT counterparts in BC patients. Combination of MT peptides from six genes might be potential as neoantigen candidates in cancer immunotherapy against BC in the future. Inflammatory modulation is inclined to be a strategy to enhance the efficacy of neoantigen-based immunotherapy.